ANALISIS KEPERCAYAAN DAN KEMUDAHAN MAHASISWA UMS TERHADAP MINAT PENGGUNAAN PRODUK FINTECH - Raharjo, Fernando Candra; Arkan, Ahmad Nazhifa; Aditya, Rahmad Galih; Hidayatullah, Rozaq Syamsul; Mahendra, Bibit Wijianarko Rezza (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
The rapid development of technology is currently seen as a means to facilitate access to information and increase the efficiency and effectiveness of resource management. Technological developments, especially in the use of the internet, have attracted public attention. Fintech, as a result of the integration of financial services and technology, is changing business processes from traditional to informal. People who previously had to transact directly and carry money can now do business remotely. This research adopts a quantitative approach with a focus on collecting statistical and objective data through scientific calculations. The research method used is a scientific approach to find solutions in scientific investigations and obtain data with specific objectives. This research uses multiple regression analysis methods to explain and summarize conditions that occur in society. Two main types of data sources were used: primary data obtained from individuals through questionnaires, and secondary data obtained from relevant literature, articles, journals and websites. The population of this study were UMS students, with sampling using a non-probability sampling approach and purposive sampling technique. This statistical test is used to analyze matters relating to validity, feasibility, multiple regression, t test, and coefficient of determination test. The results obtained show that they are in accordance with the results obtained from the questionnaire whose validity and feasibility were tested. The results of the determination test (R^2) with an Adjusted R Square value of 0.283 show that trust influences interest in investing in sharia bonds by 28.3%, and other variables not included in the model influence the remainder by 71.7%. The model feasibility test (F test) confirms that the simple linear regression model in this research is feasible. The results of the hypothesis test (T test) show that the variables of trust and comfort both have a positive effect on interest in using FINTECH products.